Effectiveness of vaccines produced by the Federal State-Financed Institution “ARRIAH” against topical genotype VII Newcastle disease viruses - S. V. Frolov; N. V. Moroz; I. A. Chvala; V. N. Irza (Ветеринария сегодня)
In 2019, the situation regarding Newcastle disease in the Russian Federation worsened radically due to the spread of NDV subgenotype VII-L throughout the country from the Primorsky Krai to the Kursk Oblast. As a result, 17 infected settlements with backyard farms where unvaccinated poultry was kept were registered. In this study, immunogenicity of the vaccines produced by the FGBI “ARRIAH”, as well as the effectiveness of various vaccination schedules to prevent genotype VII NDVs, relevant for the Russian Federation, was studied. It is known that the currently circulating ND agent is significantly more virulent compared to the viruses isolated in previous years, and it is able to bypass the immunity provided by live vaccines. Test results demonstrated that the vaccines against genotype VII NDVs produced by the FGBI “ARRIAH” are highly immunogenic, which allows to effectively prevent the disease when using them as part of a standard vaccination schedule. A 2-dose vaccination schedule using live vaccine from the La Sota strain as well as the “complete” vaccination schedule using inactivated vaccines provides immunity in 100% of chicks. The use of live vaccines in a single- and double-dose vaccination schedules prevents mortality and clinical disease in poultry, but does not prevent virus replication, while the addition of an inactivated vaccine to the immunization schedule does prevent the replication of the virulent virus. Thus, the use of domestically produced live and inactivated vaccines, primarily the ones containing the La Sota strain, with the following control of the immunity level and booster vaccination, if required, is the main tool for the disease control.